Effect of dietary probiotic supplement on growth performance and survival of Labeo rohita (hamilton) fingerlings - Sahoo, Shilpa; Acharya, U. (Journal of the Inland Fisheries Society of India, 2019)
Feeding trials were conducted in triplicate for each treatment for a period of 10 months under laboratory conditions in FRP tanks to delineate the effect of dietary probiotic (Meracid) supplementation on growth and survival rate of Labeo rohita fingerlings at four different levels. The diets were prepared utilizing the locally available ingredients to which Meracid was added at the rate of 1.0 percent (T1); 1.5 percent (T2) and 2.0 percent (T3). Diet without Meracid incorporation served as control (T0). For each treatment 10 numbers of Labeo rohita fingerlings of uniform size and weight were stocked in 500 liters of FRP tanks. The growth in terms of weight gain (%) and increment in length was found to be highest in the treatment T2 followed by the treatment (T1& T3) respectively as compared to that of control (T0). Feeding frequency in all the variants was two times a day. The fishes were fed daily @ 3% of their body weight and decreased progressively with increasing body weight during the culture period. The specific growth rate, food conversion ratio, protein efficiency ratio and survival were observed to be the highest in case of the treatment T2 followed by T1. The highest survival percentage was observed in the treatment T2 and T1 as compared to treatment T3 and T0. The results thus obtained in the present investigation indicate that incorporation of Meracid as probiotic at the rate of 1.5% (T2) to the basal diet enhances the growth and survival of Labeo rohita fingerlings. Key words Labeo rohita, probiotic, specific growth rate, survival rate.